2023
DOI: 10.3390/ijerph20021479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ozone Treatment on Health-Related Quality of Life and Toxicity Induced by Radiotherapy and Chemotherapy in Symptomatic Cancer Survivors

Abstract: (1) Background: The continuous improvement in cancer treatment has led to improvement in patients’ survival and a subsequent increase in the number of cancer survivors living with adverse side effects of cancer treatments, sometimes with a high and adverse impact on their health-related quality of life (HRQOL). Side effects of cancer treatments are frequently associated with chronic status of oxidative stress, inflammation, and/or ischemia. The potential for ozone treatment to modulate those processes and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The higher survival rate observed in the O 3 G is a reflection, among other factors, of the better quality of life. Recently, the effect of ozone treatment on health-related quality of life and toxicity induced by radiotherapy and chemotherapy in symptomatic cancer survivors was also evaluated [ 57 ]. The results demonstrated that ozone treatment has the potential to positively impact not only the treatment, as observed in our study, but also the care of cancer survivors undergoing radiotherapy and chemotherapy by significantly improving quality of life, reducing toxicity, and offering a promising therapeutic option for managing chronic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The higher survival rate observed in the O 3 G is a reflection, among other factors, of the better quality of life. Recently, the effect of ozone treatment on health-related quality of life and toxicity induced by radiotherapy and chemotherapy in symptomatic cancer survivors was also evaluated [ 57 ]. The results demonstrated that ozone treatment has the potential to positively impact not only the treatment, as observed in our study, but also the care of cancer survivors undergoing radiotherapy and chemotherapy by significantly improving quality of life, reducing toxicity, and offering a promising therapeutic option for managing chronic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we found that O 3 T could improve HRQOL using the EQ-5D-5L questionnaire (Clavo et al, 2023). However, the EQ-5D-5L questionnaire assesses the anxiety/depression dimension with only one question and it seemed justified to evaluate this dimension with a specific questionnaire focused on anxiety and Hospital anxiety and depression scale (HADS).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of cancer survivors with chronic symptoms, we found that O 3 T could decrease the grade of toxicity secondary to cancer treatments as well as improve HRQOL using the EQ-5D-5L questionnaire, which includes an anxiety/depression dimension that also showed improvement after O 3 T (Clavo et al, 2023). However, the EQ-5D-5L questionnaire assesses anxiety and depression with only one question and it seemed justified the evaluation with a specific questionnaire focused on anxiety and depression.…”
Section: Introductionmentioning
confidence: 97%
“…The benefits of radiotherapy are numerous, including a low risk of adverse effects, relatively low cost compared to other cancer treatments, and the ability to accurately target and destroy cancer cells while sparing healthy tissue. In addition, it may be used in combination with other therapies such as chemotherapy 4 , 5 and phototherapy 1 , 6 in order to improve the overall efficacy of the treatment plan. However, it should be noted that there are also certain drawbacks associated with radiation therapy.…”
Section: Introductionmentioning
confidence: 99%